Free bus travel as a policy tool for improving rural older adults’ access to opportunities - Juri Petruhhin; Margarita Kazjulja (Insights into Regional Development)
In recent decades, many countries have experienced population ageing. In Estonia, for example, the share of older adults has nearly doubled from 11.6% in 1990 to 20.3% in 2023. Although most older adults live in towns and cities, an increasing number opt to age in place, including hamlets and villages in isolated areas, far from urban facilities and services. This means that most of them use their car to get around. However, life changes such as ageing and the cessation of driving can hinder older adults’ access to basic amenities such as food shops and doctors’ offices, putting them at risk of social exclusion. In this case, public transport remains their lifeline to friends, family, and the wider community. In this paper, we conduct ride-along interviews with non-driving older adults in an isolated rural area to examine whether the introduction of free bus travel has improved their access to urban facilities and services. Our findings suggest that while the policy has been financially, psychologically, and socially beneficial for non-driving older adults, its full accessibility benefits have not been realised due to the lack of public transport service improvements. We therefore conclude that in rural areas, free bus travel should be accompanied by other measures to ensure at least a basic level of accessibility.